Malawi Drought 2015-2016 : Post-Disaster Needs Assessment - World Bank Group; United Nations; European Union (World Bank, Washington, DC, 2016)
The highly variable climate of Malawi significantly influences the amount, timing, and frequency of precipitation resulting in frequent droughts and floods. In the 2015-2016 rainfall season Malawi was hit again by prolonged dry spells. In response to the dry spells, the Government of Malawi declared a state of disaster in April 2016, and a post disaster needs assessment (PDNA) was initiated in mid-May under the leadership of the Government of Malawi, with the assistance of the World Bank and the United Nations (UN). The PDNA also developed a recovery strategy for the 2015-2016 drought by defining and aligning a national recovery vision to long-term development objectives and by formulating a multi-sector framework of recovery interventions, while ensuring building-back-better and integrating gender and environmental considerations in the recovery strategy. The assessment process utilized a combination of secondary data from similar assessments that were ongoing at that time, along with primary data collection to fill in gaps and validate impacts. The PDNA defines a strategy for recovery, including its financial implications, while making recommendations to improve future drought resilience. The report is structured as follows: chapter one explains the background and objective of the PDNA; chapter two describes the country profile; chapter three provides an analysis of the drought and an overview of the humanitarian consequences and the government’s immediate response; chapter 4 describes the approach and methodology of the PDNA; chapter five summarizes the overall damages and losses caused by the drought, as well as the recovery strategies and needs for each of the sectors considered in the assessment; chapter six describes the overall macroeconomic impact of the drought; chapter seven presents the human and social impact of the drought, including a gender analysis of specific sector recommendations for recovery; chapter eight provides details for the drought recovery strategy on the basis of the sector analysis; chapter nine analyses the challenges and lessons learned from the ongoing drought and recommendations for drought risk reduction and resilience; chapter ten summarizes the next steps and the way forward.